Pengaruh Gaya Kepemimpinan Kepala Sekolah dan Persepsi Sertifikasi Terhadap Kinerja Guru melalui Variabel Intervening Motivasi Berprestasi Jenjang SMP Negeri Sekabupaten Konawe Utara - Monovatra Predy Rezky; Samdin Samdin; Muh. Nur (Publikasi Indonesia, 2022)
The performance of quality teachers can have a good impact on the realization of an educational institution. This study intends to analyze the principal's leadership style and the perception of certification on teacher performance through the intervention variable of achievement motivation in SMP Negeri SeKabupaten North Konawe. The population in this study were all teachers who were recorded to be active in North Konawe Regency, as many as 42 people. The population determination is by Cluster Area Random Sampling and continued by taking samples using the Slovin technique. The analytical tool used is Smart PLS software. According to the results of the study, it can be concluded that leadership style has a good and big impact on teacher performance, leadership style has a good and big impact on achievement motivation, perceptions of certification have a good and big impact on teacher performance, perceptions of certification have a good and big impact on teacher performance and have a big impact on achievement motivation has a positive and significant impact on achievement motivation and has a good and large impact on teacher performance. Leadership style has a good and large impact on teacher performance. Cognition certification has a good and large impact on the performance of junior high school teachers in Oheo Street, North Conaway County Intervention Variables of Teacher Achievement Motivation by Country.